Cognitive and Balance Performance among Elderly in Nursing Home - Mathilda Albertina; Herdiman Bernard Purba; Siti Annisa Nuhonni (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Cognitive disorders have associated with incidence of fall. Cognitive problem is more frequent in elderly living in nursing homes compared to those who live in community. The aim of this study is to determine correlation between balance performance and cognitive status among elderly in nursing home.Methods: This study was conducted in a nursing home in Jakarta. Balance performance was evaluated using Timed Up and Go (TUG) test and Berg Balance Scale (BBS), while cognitive status was examined using Mini Mental State Examination (MMSE).Results: There were 35 participants, consisted of male 10(28.6%) and female 25(71.4%) with median aged 69 years old, included in this study. Median MMSE result was 21 (6-30). The median result of TUG was 14.13 (9.66-88.50) seconds. The median BBS result was 50 (18-56). MMSE have negative strong correlation with TUG (r = -0.693; p = 0.000) and positive strong correlation with BBS (r = 0.640; p=0.000).Conclusion: Cognitive function has strong correlation with balance performance among elderly in nursing home. Therefore, cognitive aspect should be included in fall prevention program.Keywords: Balance, cognitive, elderly, nursing home